Could Thyroid Disorders Be Better Understood and Dealt as a Thyroid Syndrome: Thyroid disorder new insight - Patil, Dr. Sushma; Patil, Dr. Vikrant (International Journal of Innovative Research in Medical Science, 2020)
Thyroid disorders are common worldwide. Thyroid dysfunction, both hypo- and hyperthyroidism may increase the risk of cardiovascular disorders. Current thyroid function tests may have limitations since they only measure the total or free T4 and/or T3 and TSH serum concentrations in peripheral blood and not the effect of T4 or T3 serum on different specific target tissues. Several comorbid conditions can interfere with the absorption or increase the clearance of levothyroxine. Among patients treated with thyroid replacement, under or overmedicated may-be at risk for adverse health consequences. A wide range of drugs may interfere with levothyroxine absorption, metabolism, and action. Patients report a lack of well-being, despite reaching euthyroid reference range of TSH, with psychological distress. If we will consider Thyroid related conditions as a syndrome then research perspective at the pathophysiology, interrelation between symptoms and comorbidities will be much broader that can lead researchers to get insights of different pathways in which thyroid gland functioning can be perceived and dealt therapeutically. The deliberation of thyroid disorder as a syndrome can affluence our knowledge of correlating cofounders, action of thyroid hormones on target tissues, underlying cause and thyroid health.